Plethysmographic and anthropometric validation of a 3D body image digitizer to determine body dimensions - URQUIDEZ ROMERO, RENE (Elsevier, 2018)
Much is known about leg/foot movement times when there is a single target constraint - that in the direction ofthe movement. We report two experiments that investigated the eﬀects of an additional constraint that wasperpendicular to the direction of the movement. In Experiment 1, a standard Fitts' task was used but with targetsthat varied in height and, in Experiment 2, we used the Drury tracking task of moving between lines of varyingtrack widths. Results were diﬀerent to those of arm/hand movements. In experiment 1 the eﬀects of the Indexesof Diﬃculty (ID) in the direction of, and perpendicular to, the movement direction, were linearly additive. Thisis compared to the ‘greater ID model’ that gives a good description of arm movements. When tracking betweenparallel lines, foot performance is poor compared to arm performance when error rates are controlled. The Drurymodel well describes data for arm and foot movements, when the error rates are controlled, but initial error ratesincrease rapidly with decrease of target width and hence the leg/foot system has diﬃculty in control at highervalues of amplitude to track width ratio.Relevance to industry: The foot is commonly used for controlling a device. This research demonstrates the eﬀectof having limited width of a target perpendicular to the direction of movement of the foot/leg. Performance iscompared to that of the hand/arm system.